Effect of ultrasound-guided percutaneous neuromodulation applied to the femoral nerve on pain and range of motion in patients with anterior knee pain: A case study - García-Bermejo, Paula; Romero-Morales, Carlos; de-la-Cruz-Torres, Blanca (Revista Fisioterapia Invasiva / Journal of Invasive Techniques in Physical Therapy, 2020)
Introduction Anterior knee pain (AKP) is one of the most frequent reasons for physical therapy consultations, remaining a difficult treatment challenge for professionals. The aim of this study was to evaluate the effects of an intervention using ultrasound-guided percutaneous neuromodulation (US-guided PNM) applied to the femoral nerve on pain and knee flexion range of motion (ROM), in patients with unilateral chronic anterior knee pain.Methods Eight patients received a single intervention of NMP-e on the femoral nerve of the symptomatic knee. The level of pain and ROM were measured before, immediately after and 24 hours after the intervention.Results A decrease in pain and an increase of ROM were observed after the intervention and at 24 hours. For pain values, a medium effect size was observed (ES = 0.63 ± 0.43) after the intervention, and a large effect size (ES = 1.73 ± 0.44) was found at 24h. Concerning ROM, the effect size was large at both moments (ES = − 1.30 ± 1.14; −1.76 ± 0.80, respectively).Conclusion A single intervention of US-guided PNM on the femoral nerve produces a decrease of pain and increases the ROM, which is greater 24h after the stimulation.Level of Evidence Level II-3.Introducción El dolor anterior de rodilla (DAR) es uno de los principales motivos de consulta y su tratamiento continúa siendo un reto para el fisioterapeuta. El objetivo del estudio fue evaluar los efectos de una intervención de neuromodulación percutánea ecoguiada (NMP-e) en el nervio femoral sobre el dolor y el rango de movimiento (ROM) de flexión de rodilla, en pacientes con dolor anterior de rodilla unilateral crónico.Método Ocho pacientes recibieron una única intervención de NMP-e sobre el nervio femoral de la rodilla sintomática. El nivel de dolor y el ROM fueron medidos antes, inmediatamente después y a las 24 horas de la intervención.Resultados Se produjo un descenso del dolor y un aumento del ROM tras la intervención y a las 24 horas. Respecto al dolor, el tamaño del efecto fue mediano (ES = 0,63 ± 0,43) tras la intervención y grande (ES = 1,73 ± 0,44) a las 24h. Respecto al ROM, el tamaño del efecto fue grande en ambos momentos (ES = -1,30 ± 1,14; -1,76 ± 0,80, respectivamente).Conclusión Una única intervención de NMP-e sobre el nervio femoral produce una disminución del dolor y aumenta el ROM, mayor a las 24h de la estimulación.Nivel de evidencia Nivel II-3.
Keywords: anterior knee pain; femoral nerve; percutaneous neuromodulation; ultrasound